Chemical indicators for pollution detection in terrestrial and aquatic ecosystems - Zaghloul, Alaa (2021)
Pollution is objectionable changes in a given ecosystem trailing to potential health hazards. Assessment of pollution levels is continually recognized by several pollution indicators, biological, chemical, and/or physical. Chemical indicators always validate fair information about the evenness between ecosystem components. Chemical indicators include pH, quality criterion index, kinetics, oxidation-reduction potential, reactive carbon, total organic C, total residues, dissolved oxygen (DO), chemical oxygen demand (COD), biological oxygen demand (BOD), phosphate (P), nitrogen (N2), anhydrous ammonia (NH3), nitrate (NO3), and copper (Cu2+).